New perspectives on M&A research - LI, Zhefei (Institutional Knowledge at Singapore Management University, 2019)
Corporate acquisition is among the most important strategic tools wielded by managers to achieve competitive advantage. Acquisition may create strategic values for the acquirer by gaining market power through industry consolidation, diversifying into rapidly growing industries, entering into emerging markets, and most importantly by combining unique valuable resources from acquirer and target. Despite the many appealing aspects of the motive for acquisition, however, meta-analytical studies suggest that though highly beneficial for the target firm’s shareholders, acquisition on average destroys acquirer shareholder values. to understand the determinants of acquisition performance success, it becomes imperative to study the antecedents as well as consequences of acquisition. Existing literature has found scores of potential culprits including agency behavior, position in merger wave, managerial hubris, poor acquisition capability in post-acquisition integration, and loss of valuable human capital resources among others. Beyond acquisition performance, acquisition also results in many other intended and unintended consequences such as employee turnover and CEO departures. What may affect various acquisition outcomes? How do these outcomes affect future acquisition decisions? In my dissertation, I look at two additional factors that may affect the success of acquisition by conducting two empirical studies on the antecedents as well as consequences of acquisition using behavioral and resource based theories. I further explore the connections between the antecedents and outcomes of acquisitions. In the second chapter, incorporating risk taking, I focus on the influences of alliance and acquisition performance feedback on the rate of future acquisitions. The Behavioral Theory of the Firm (BTF) and performance feedback theory have been used to explain corporate acquisition behaviors both at the organizational and deal levels. However, extant literature does not agree on the relationship between acquisition performance feedback and likelihood of subsequent acquisition. Firms may search in different directions in response to acquisitions failures. Moreover, we still lack a clear understanding of the behavioral influences on the various sourcing mechanisms. To address these questions, we built on both the BTF and prospect theory to propose a search hierarchy among corporate sourcing methods. We posit that the general search direction in corporate development follows from simple to complex and from economical to costly. We hypothesize that, under the duo influences of problemistic search and risk taking, deal performance feedback is negatively related to future acquisitions. We further investigate the interaction between alliance and acquisition performance feedback on future acquisitions. In the third chapter, given the importance of human capital retention and turnover in the success of acquisition, I examine how target firm’s knowledge base may affect acquirer’s decision to retain the target’s CEO. Drawing upon the firm-specific resources and strategic human capital literatures, we develop the argument that the level of firm-specific knowledge in an acquisition target may affect the likelihood of the target’s CEO being retained after an acquisition. Specifically, due to the important role of target CEOs in preserving the value of and integrating firm-specific knowledge, we expect a positive relationship between a target’s pre-acquisition firm-specific knowledge level and the likelihood that its CEO is retained. Furthermore, we argue that this relationship is strengthened by the target’s pre-acquisition performance, which signals a higher value of firm-specific knowledge, and the target CEO’s tenure, which is positively associated with both the benefit of retaining and the cost of replacing the CEO. Using a sample of acquisitions involving US target firms acquired between 1995 and 2006, we find support for our hypotheses.